1992
DOI: 10.1152/ajpgi.1992.262.4.g774
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of nitric oxide from muscle cells by VIP: prejunctional enhancement of VIP release

Abstract: The source of nitric oxide (NO) and its role in neurally induced relaxation was examined in smooth muscle of the stomach and tenia coli. Field stimulation of gastric muscle strips was accompanied by frequency-dependent relaxation, vasoactive intestinal peptide (VIP) release, and NO production: the NO synthase inhibitor, NG-nitro-L-arginine (L-NNA) completely inhibited NO production and partly inhibited VIP release (52-54%) and relaxation (58-88%); inhibition of all three functions was reversed by L-arginine bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
133
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 12 publications
11
133
3
Order By: Relevance
“…The most important evidence that VIP does not act through NO is that L-NAME prevented relaxations induced by vagal stimulation but did not affect those induced by VIP. Thus, even if VIP is released by vagal stimulation, it does not act through stimulation of NO production from neurones or smooth muscle cells, as has been suggested (Grider et al, 1992). This would hold even if these tissues contain isoforms of NOS not detected by our antibody staining.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The most important evidence that VIP does not act through NO is that L-NAME prevented relaxations induced by vagal stimulation but did not affect those induced by VIP. Thus, even if VIP is released by vagal stimulation, it does not act through stimulation of NO production from neurones or smooth muscle cells, as has been suggested (Grider et al, 1992). This would hold even if these tissues contain isoforms of NOS not detected by our antibody staining.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, electrical field stimulation of muscle strips from the guineapig and rat gastric fundus causes release of VIP-like immunoreactivity (Grider & Makhlouf, 1987;D'Amato et al, 1992). It has also been suggested that VIP and NO are co-transmitters of gastric relaxation in the guinea pig, rat and ferret (Li & Rand, 1990;Boeckxstaens et al, 1992;Grider et al, 1992;Said, 1992;Grider & Jin, 1993;Grundy et al, 1993) and internal anal sphincter in the opossum (Chakder & Rattan, 1993). One possibility is that VIP acts partly through stimulation of NO formation, as has been suggested in the smooth muscle cells of the guinea pig stomach (Grider et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 The NO level was significantly decreased in 2-year old rats as compared to 6-week old rats in the DC (P = 0.001), but not in the AC (P = 0.791) (Fig. 6A).…”
Section: Nitric Oxide Levelsmentioning
confidence: 92%
“…Based on the use of inhibitors of NO synthase (Rees et al, 1990;Moore et al, 1990) such as NG-monomethyl L-arginine (L-NMMA) or N0-nitroarginine (L-NOARG), NO has been proposed as a mediator of the non-adrenergic, non-cholinergic (NANC) relaxation of the intestinal smooth muscle, including that of rat or guinea-pig stomach and duodenum and the canine ileo-cecal juction and duodenum (Li & Rand, 1990;Bult et al, 1990;Toda et al, 1990;Desai et al, 1991;Irie et al, 1991). In addition, NO synthase has been located in the myenteric plexus and other neuronal structures of the rat gastro-intestinal tract (Bredt et al, 1990;Belai et al, 1992), although the contribution of the nitrergic neuronal enzyme to the overall NO synthase activity in the gastrointestinal tissues is not yet fully clear (Whittle et al, 1992;Grider et al, 1992; Sanders & Ward, 1992;Tepperman et al, 1993).…”
Section: Introductionmentioning
confidence: 99%